ANALISIS KOMPETENSI DAN MOTIVASI KERJA PENGARUHNYA TERHADAP KINERJA PEGAWAI - Muwafik, Mohammad (Magister Manajemen, Fakultas Pasca Sarjana, Universitas Komputer Indonesia)
This study aims to get the results of the study background of frequent occurrence and out of the employee, the employee's performance has not fulfilled what is expected by the leadership, the study include: (1) competence, motivation and performance of employees, (2) The relationship of competence and motivation, (3) the effect of competence on employee performance, (4) the effect of motivation on employee performance.This type of research is descriptive and verification. The population is Sinarmas Bank branch employees Cirebon. The number of samples taken as many as 215 samples are taken with the withdrawal of a random sample method. Model the effect of using Structurall Equation Modeling (SEM) with LISREL 8.80. The results of this study have suitability in explaining linkages between variables. the results showed that: Competence, motivation and performance of employees are in the good category. Competence and motivation are intimately connected, competencies influence on employee performance, and motivation influence on employee performance.